The Effect of a Variety of Anaerobic Exercises on the Ability and Anaerobic Capacity and Rapid Individual Attack of Young Players in Handball - Reza Talib Hilail (Journal of Global Pharma Technology, 2016)
The importance of research lies in the preparation of a variety of anaerobic exercises and their impact on anaerobic ability and capacity that directly participate in the performance of the individual handball rapid attack of young players. The problem of research: focused on the lack of use of trainers for the various anaerobic exercises based on the overlap in energy production systems, there is a weakness in the use of anaerobic exercises.It is necessary to study the effect of the various anaerobic exercises on the basis of the proper scientific connection between science and science. And training in order to achieve the desired objectives of the training process.The objective of the research is to:Preparing a variety of anaerobic exercises in handball.To recognize the effect of the various anaerobic exercises on the anaerobic ability and capacity and individual quick attack of young players in handball.The research hypotheses included the following:The various anaerobic exercises have an impact on the anaerobic ability and capacity and individual quick attack of young players in handball.There is a preference for influencing the various anaerobic exercises in the anaerobic ability and capacity and individual rapid attack of young players in handball between the experimental and control groups in the posttest tests and for the benefit of the experimental group.As for the research methodology and field procedures:The researchers used the experimental method to solve the research problem. The research community was identified by 16 young Kufa youth handball players and they were divided into two groups (experimental and control) equally by random method (drawing method). After preparing the training curriculum the pilot group underwent training on the use of a variety of anaerobic exercises, while the control group used the usual training method for the trainer. After eight weeks, the tests were carried out. And then the data using appropriate statistical methods address.As for the most important conclusions and recommendations, the most important conclusions were the following:Various anaerobic exercises have helped to develop anaerobic capacity.The various anaerobic exercises have helped to develop anaerobic capacity.The development of anaerobic capacity and anaerobic capacity has been positively reflected on the development of individual rapid handball attack.Keywords: Anaerobic exercises, Ability, Anaerobic capacity, Rapid individual and handball.